2017
DOI: 10.1007/s00590-017-2057-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of functional outcome of bipolar hip arthroplasty and total hip replacement in displaced femoral neck fractures in elderly in a developing country: a 2-year prospective study

Abstract: Level II, lesser-quality randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Hip fractures place a large burden on our health-care system. 3,4,6 There is substantial controversy regarding the indications for THA and HHA as well as what should be the preferred treatment in different circumstances, 3,7,12,13 including in different age subgroups. Our study found that patients aged 65 years and older who were treated with a THA had decreased mortality when compared with propensity score–matched patients after HHA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip fractures place a large burden on our health-care system. 3,4,6 There is substantial controversy regarding the indications for THA and HHA as well as what should be the preferred treatment in different circumstances, 3,7,12,13 including in different age subgroups. Our study found that patients aged 65 years and older who were treated with a THA had decreased mortality when compared with propensity score–matched patients after HHA.…”
Section: Discussionmentioning
confidence: 99%
“…Displaced femoral neck hip fractures are currently treated with either total hip arthroplasty (THA) or hip hemiarthroplasty (HHA); however, treatment selection is controversial. 7-12 Guidelines in the United Kingdom recommend THA for patients who can ambulate outside the home, have no cognitive impairment, and are medically fit for the procedure. 13 Formal guidelines in other countries, such as the United States, are yet to be formulated.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the levels of various cytokines, such as interleukin-6 are elevated [27]. Additionally, patients with CKD have higher levels of D-dimer, CRP, fibrinogen, factor VII, and factor VIII [28,29] Conclusions Downloaded from http://meridian.allenpress.com/japma/article-pdf/doi/10.7547/20-007/2557520/20-007.pdf by guest on 04 November 2020 JAPMA Online Early DOI: 10.7547/20-007 This Original Article has been reviewed, accepted for publication, and approved by the author. It has not been copyedited, proofread, or typeset and is not a final version.…”
Section: The Clinical Outcomes Of Total Hip Arthroplasty In Renal Tramentioning
confidence: 99%
“…During study selection, we excluded some RCTs, including five studies that incorporated patients younger than 75 years old [7,[34][35][36][37] and two studies included patients unable to live independently [38,39], and two studies included patients unable to live independently [40,41]. There were a total of 631 participants in the nine trials included in the study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…THA and HA are widely used in the displaced femoral neck fractures (DFNF) [5]. HA has advantages of shorter operation times, less blood loss, less technical demand, less economic burden, and a lower post-operative dislocation rate [7][8][9][10]. THA procedures are associated with better hip function, less acetabulum erosion, and a lower revision rate, but more substantial surgical strike and a higher post-operative dislocation rate [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%